The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fbioe.2022.842382
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Intervertebral Fusion Process After Anterior Cervical Discectomy and Fusion: A Finite Element Study

Abstract: Introduction: Anterior cervical discectomy and fusion (ACDF) is a widely accepted surgical procedure in the treatment of cervical radiculopathy and myelopathy. A solid interbody fusion is of critical significance in achieving satisfactory outcomes after ACDF. However, the current radiographic techniques to determine the degree of fusion are inaccurate and radiative. Several animal experiments suggested that the mechanical load on the spinal instrumentation could reflect the fusion process and evaluated the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…As shown in Figure 2, the predicted segmental ROM of the present intact cervical spine model was within the standard deviation of the previous experimental data (Panjabi et al, 2001;Lee et al, 2016;Liu et al, 2016). The maximal intradiscal pressure of adjacent levels was consistent with in vitro experiments and previous finite element results (Welke et al, 2016;Zhou et al, 2021), and the facet contact force (FCF) of the model was also in agreement with the literature (Wu et al, 2019;Shen et al, 2022). All indicated that the present model was reliable in representing a healthy individual and could be used for further experiments.…”
Section: Validation Of the Intact Cervical Spine Modelsupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in Figure 2, the predicted segmental ROM of the present intact cervical spine model was within the standard deviation of the previous experimental data (Panjabi et al, 2001;Lee et al, 2016;Liu et al, 2016). The maximal intradiscal pressure of adjacent levels was consistent with in vitro experiments and previous finite element results (Welke et al, 2016;Zhou et al, 2021), and the facet contact force (FCF) of the model was also in agreement with the literature (Wu et al, 2019;Shen et al, 2022). All indicated that the present model was reliable in representing a healthy individual and could be used for further experiments.…”
Section: Validation Of the Intact Cervical Spine Modelsupporting
confidence: 91%
“…Fourth, this study simplifies the musculoskeletal system, and the results under this ideal condition did not fully reflect the actual postoperative situation. Although this study aimed to provide a biomechanical reference for clinics, the manipulation of the muscular–ligamentous system in this finite analysis was based on previous literature ( Fu et al, 2022 ; Huang et al, 2022 ; Shen et al, 2022 ; Zhang et al, 2022b ). Last, linear elastic materials were adopted for the cervical vertebral body and intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, biomechanical research works found that the plate could provide better segmental stability than Zero-profile spacer [27,28], which was consistent with our findings. Loss of CL is often considered to cause progressive degenerative cervical spondylosis (DCS) and also be responsible for neck pain and neurological dysfunction [5,[29][30][31][32]. However, the higher LOC after ACDF with ZP device, especially the data of LOC in CL as high as 48.13% given by Sun et al [13] in the 5-year followup, makes us worry about the condition of patients in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…The success of cervical surgery often depends directly on the progress of fusion [27]. From a biomechanical point of view, additional external or internal support should be employed to prevent excessive movement of cervical cages[28].…”
Section: Discussionmentioning
confidence: 99%